A modalidade oral e os cadernos de inglês do Estado de São Paulo: proposta de complementação - Santos, Juliana Munhoz dos (2015)
This research aims to investigate what the senses and meanings that the English public school teacher attributes to the oral modality at the Public School and how teachers evaluate a complementary oral material with oral activities. This study was conducted from the perspective of Critical Applied Linguistics, based on Moita Lopes (2006). It is based on socio-cultural-historical theory (VYGOTSKY, [1934] 2013) and in oral concepts discussed by Marcuschi (2008); Savignon (1997) and Byrne (1976). The methodology used is the critical-interpretive (MOITA LOPES, 1994; 1996); and the data were collected through an online questionnaire, a reflective conversation on the material created by the researcher and a reflective conversation about orality in English classes. For analysis and discussion of the results, it was used the thematic content category by Bronckart ([1997] 1999), evidenced by lexical choices of the participants, about the orality and about the complementary material as well. The results can guide a more specific work about the oral modality in English language classes at the public schools, enabling the transformation of practices in the classroom